2019
DOI: 10.32674/jis.v9i4.606
|View full text |Cite
|
Sign up to set email alerts
|

Bahamians as International Adult Learners Determined for Academic Success

Abstract: The purpose of this study is to explore the factors that impact the experience of Caribbean nontraditional adult learners encounter while pursuing higher education in the United States and perceived support systems needed by Caribbean adult learners to be successful. On this premise, this qualitative study was conducted. A total of 15 Bahamian students participated. Data was collected via semi structured interviews and analyzed utilizing open coding. The major themes that emerged with regards to influential fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
3
0
2
Order By: Relevance
“…Kajian tentang adaptasi dan tantangan yang dihadapi oleh mahasiswa internasional telah dilakukan di berbagai negara, seperti Malaysia, Rusia, Filipina, Australia, Inggris, Amerika Serikat dan India (Hunter-Johnson & Niu, 2019;Le & McKay, 2018;Novoselova, Bondareva, Semanina, Chistyakov & Zetkina, 2020;Singh, 2019). Penelitian tentang pengalaman mahasiswa Cina dan Vietnam saat berkuliah di Australia menunjukkan bahwa mereka mendapatkan tutor yang berasal dari negara-negara yang bukan penutur berbahasa Inggris yang aksen bahasa Inggrisnya susah dipahami.…”
Section: Adaptasi Dan Tantangan Mahasiswa Internasionalunclassified
See 1 more Smart Citation
“…Kajian tentang adaptasi dan tantangan yang dihadapi oleh mahasiswa internasional telah dilakukan di berbagai negara, seperti Malaysia, Rusia, Filipina, Australia, Inggris, Amerika Serikat dan India (Hunter-Johnson & Niu, 2019;Le & McKay, 2018;Novoselova, Bondareva, Semanina, Chistyakov & Zetkina, 2020;Singh, 2019). Penelitian tentang pengalaman mahasiswa Cina dan Vietnam saat berkuliah di Australia menunjukkan bahwa mereka mendapatkan tutor yang berasal dari negara-negara yang bukan penutur berbahasa Inggris yang aksen bahasa Inggrisnya susah dipahami.…”
Section: Adaptasi Dan Tantangan Mahasiswa Internasionalunclassified
“…Hambatan lainnya adalah masalah bahasa saat proses perkuliahan di kelas, serta adaptasi dengan pergaulan sosial, khususnya kesulitan bersosialisasi dengan mahasiswa domestik/lokal (Le & McKay, 2018). Berbeda dengan hasil penelitian terhadap lima belas (15) mahasiswa internasional dari Bahamian yang kuliah di Amerika Serikat, mereka mengungkapkan bahwa tantangan mereka sebagai mahasiswa internasional berkaitan dengan keuangan dikarenakan biaya kuliah yang mahal (Hunter-Johnson & Niu, 2019). Adaptasi bahasa tidak menjadi masalah untuk -28 -mahasiswa Bahama di Amerika Serikat, berbeda dengan hasil penelitian pada mahasiswa Asia yang belajar di negara barat, di mana masalah adaptasi bahasa dilaporkan dalam banyak penelitian (Chen, 2018;Le & McKay, 2018;Luo, 2019;Singh, 2019).…”
Section: Adaptasi Dan Tantangan Mahasiswa Internasionalunclassified
“…Third, at the institutional level, administrators also have an important responsibility in developing international student confidence. There are many challenges that can deflate an international student, including visa, financial, and health concerns, among others (Hunter-Johnson & Niu, 2019). Removing obstacles, or minimally providing kind customer support, can build a student's confidence as they navigate foreign institutional norms.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…Some researchers have suggested that university lecturers saw the importance of demonstrating care by developing open, honest, respectful, fair, encouraging and supportive relationships with students (Anderson & Carta-Falsa, 2002;Fitzmaurice, 2008). Situated within the microsystem (Bronfenbrenner, 2005), Hunter- Johnson (2019) proposed that relationships with academic staff were important, especially for international students who are lacking family presence. Lähteenoja and Pirttilä-Backman (2005) suggested that attempts to promote student integration, thus creating a safe environment and promoting positive learning opportunities, can be regarded as a specific form of caring which was beneficial for students, although they recognised that not all academics hold this view.…”
Section: Proximal Processes and Academicsmentioning
confidence: 99%
“…International students can often find themselves with no established reference points for negotiating their new environment, which is compounded by the loss of previous community support in their home country (Dai & Garcia, 2019;Hunter-Johnson, 2019;Johnson, Seifen-Adkins, Sandhu, Arbles, & Makino, 2018). This model is particularly useful for explaining the sense of isolation, strangeness and loneliness experienced by participants, since transitioning from one bioecological system to another can impact and challenge one's wellbeing, knowledge, self-assurance and confidence.…”
Section: Introductionmentioning
confidence: 99%